Modeling orthodox christian theological education in middle eastern conflict zones: a study of epistemological, dogmatic, hermeneutical, and ethical dimensions - Murni Kasih Zebua; M. Agung Rahmadi; Luthfiah Mawar; Helsa Nasution; Nurzahara Sihombing (JPGI (Jurnal Penelitian Guru Indonesia), 2025)
This study offers an in-depth examination of the construction of Orthodox Christian theological education in Middle Eastern conflict zones, employing Confirmatory Factor Analysis under a MASEM framework to investigate four central dimensions: patristic epistemology, dogmatic rationality, the hermeneutics of tradition, and ethics. Through a meta-analytic approach that integrates online data from 847 institutional documents and 1,523 virtual respondents across Syria, Lebanon, Jordan, Palestine, and Iraq from 2018 to 2024, the study identifies a structural model that demonstrates excellent goodness-of-fit indices, with χ²/df = 2.17, CFI = 0.946, TLI = 0.938, RMSEA = 0.054, and SRMR = 0.041. Patristic epistemology exhibits the highest loading factor (λ = 0.89, CR = 12.45, p < 0.001), with a substantial influence on academic resilience (β = 0.76, p < 0.001). In contrast, dogmatic rationality significantly strengthens theological identity stability (β = 0.68, p < 0.001). The hermeneutics of tradition reinforce communal cohesion (β = 0.71, p < 0.001), and ethics function as a significant mediator between theological constructs and altruistic behaviour in conflict zones (β = 0.63, p < 0.001). These findings extend the works of Makrides (2009), Iran (2020), and Papanikolaou (2012) by integrating psychological dimensions of education into Orthodox theology, while simultaneously generating a new empirical model that aligns patristic tradition with adaptive responses to collective trauma, resulting in an innovative theoretical framework for Orthodox theological education in conflict areas that balances doctrinal steadfastness with contextual elasticity.